Dead Collections: Exploring Chronic Illness in Academic Libraries through the Metaphor of Vampires - Snyder Broussard, Mary (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2024)
Isaac Fellman’s Dead Collections: A Novel (2022) portrays a fictional archivist named Sol who experiences chronic illness in the form of vampirism. While he has many symptoms including cold skin and reliance on weekly blood transfusions, it is his life-threatening photophobia (aversion to sunlight) that becomes a serious impediment to commuting to and from work. While Sol and his vampirism are clearly fictional, the novel accurately depicts working in libraries with a chronic illness. This article compares and connects Dead Collections to the growing body of literature on library workers with disabilities and chronic illness, particularly articles that give voice to those with relevant lived experiences. Highlights of this discussion include the topics of non-apparent illnesses, disclosure, passing, reactions to disability among coworkers and supervisors, and the promises and disappointments of the Americans with Disabilities Act.